Manufacturing method of bipolar electrode laminate, and manufacturing method of bipolar battery
By depositing electrode composite materials on current collector layers and dissolving the electrolyte component to form an electrolyte solution, the method addresses density challenges in bipolar batteries, achieving desired layer densities with fewer steps and providing a direct electrolyte for the battery.
Patent Information
- Application Number
- JP2023094115
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2043-06-07
AI Technical Summary
In bipolar batteries, achieving desired densities for both positive and negative electrode active material layers is challenging due to their differing flexibilities, leading to preferential compression during manufacturing, and existing methods require multiple pressing steps.
A method involving the deposition of electrode composite materials on current collector layers, followed by pressing and dissolving the electrolyte component with a solvent to form an electrolyte solution, allowing for controlled density and fewer manufacturing steps.
This approach enables bipolar electrode laminates with desired densities for both layers while reducing manufacturing steps, and the electrolyte solution can be used directly as the battery electrolyte.
Smart Images

Figure 2024175966000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to methods of making bipolar electrode stacks and methods of making bipolar batteries. [Background technology]
[0002] 2. Description of the Related Art Bipolar electrodes have been known in the past, each of which has a positive electrode active material layer on one surface of a current collector and a negative electrode active material layer on the other surface of the current collector.
[0003] For example, Patent Document 1 discloses a method for producing a bipolar electrode, the method including the steps of: applying a first electrode mix slurry to form a first active material layer in a first area on a first surface of a current collector; applying a second electrode mix slurry to form a second active material layer in a second area on the inner periphery of the first area on a second surface of the current collector; applying an electrical insulating agent slurry to form an end electrical insulating layer in a third area on the second surface of the current collector that is in contact with the second area on the outer periphery of the second area; drying the first electrode mix slurry, the second electrode mix slurry, and the electrical insulating agent slurry; and simultaneously pressing the dried first electrode mix slurry, the second electrode mix slurry, and the electrical insulating agent slurry to form the first active material layer, the second active material layer, and the end electrical insulating layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2019 / 230323 Summary of the Invention [Problem to be solved by the invention]
[0005] In bipolar batteries, it is desirable for the positive electrode active material layer to have a high density in order to achieve high capacity, while it is sometimes desirable for the negative electrode active material layer to have a low to medium density in order to absorb the expansion and contraction of the negative electrode active material.
[0006] In the manufacture of a bipolar battery, a layer for forming a positive electrode active material layer (hereinafter, in this disclosure, a positive electrode active material layer precursor) and a layer for forming a negative electrode active material layer (hereinafter, in this disclosure, a negative electrode active material layer precursor) may be made of different materials, and in that case, these layers have different flexibility. Therefore, when the negative electrode active material layer precursor and the positive electrode active material layer precursor are dried and pressed, the softer one of them is preferentially compressed, and the negative electrode active material layer and the positive electrode active material layer formed by pressing may not have the desired density.
[0007] As a method for solving this problem, a method is considered in which a positive electrode active material layer precursor is formed on one surface of a positive electrode current collector layer, a negative electrode active material layer precursor is formed on one surface of a negative electrode current collector layer, and then the two are pressed to form the respective electrode active material layers, and the surfaces of both current collector layers on which the electrode active material layers are not formed are opposed to each other and bonded to produce a bipolar electrode. However, this method requires two pressing steps, which increases the number of production steps.
[0008] An object of the present disclosure is to provide a method for producing a bipolar electrode stack that can provide a positive electrode active material layer and a negative electrode active material layer with desired densities and that involves fewer production steps, and a method for producing a bipolar battery that includes producing such a bipolar electrode stack. [Means for solving the problem]
[0009] The present inventors have found that the above problems can be solved by the following means. <Aspect 1> 1. A method for producing a bipolar electrode stack having a first electrode active material layer, a current collector layer, and a second electrode active material layer in this order, the method comprising the steps of: providing a first electrode mix comprising a first electrode active material and a first binder, and a second electrode mix comprising a second electrode active material, a second binder, and an electrolyte component; depositing the first electrode mixture on a first surface of the current collector layer to form a first electrode active material layer precursor, and depositing the second electrode mixture on a second surface of the current collector layer to form a second electrode active material layer precursor; pressing a laminate including the first electrode active material layer precursor, the current collector layer, and the second electrode active material layer precursor; and After the pressing, dissolving the electrolyte component in the second electrode active material layer with a solvent to produce an electrolyte solution. <Aspect 2> 2. The method of claim 1, wherein the electrolyte component is a lithium salt. <Aspect 3> 3. The method of any one of the preceding aspects, wherein the first electrode active material layer is a positive electrode active material layer and the second electrode active material layer is a negative electrode active material layer. <Aspect 4> A method for producing a bipolar battery, the method comprising producing the bipolar electrode stack by the method according to any one of aspects 1 to 3. Effect of the Invention
[0010] According to the present disclosure, it is possible to provide a method for producing a bipolar electrode stack that can provide a positive electrode active material layer and a negative electrode active material layer with desired densities and that involves fewer production steps, and a method for producing a bipolar battery that includes producing such a bipolar electrode stack. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view showing a laminate before the electrolyte component is dissolved in a solvent. [Diagram 2] FIG. 2 is a cross-sectional view showing the bipolar electrode stack after the electrolyte components have been dissolved in a solvent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.
[0013] <<Method for manufacturing bipolar electrode laminate>> The disclosed method for manufacturing a bipolar electrode laminate having a first electrode active material layer, a current collector layer, and a second electrode active material layer in this order includes providing a first electrode mixture including a first electrode active material and a first binder, and a second electrode mixture including a second electrode active material, a second binder, and an electrolyte component; depositing the first electrode mixture on a first surface of the current collector layer to form a first electrode active material layer precursor, and depositing the second electrode mixture on a second surface of the current collector layer to form a second electrode active material layer precursor; pressing the laminate including the first electrode active material layer precursor, the current collector layer, and the second electrode active material layer precursor; and, after pressing, dissolving the electrolyte component in the second electrode active material layer with a solvent to produce an electrolyte solution.
[0014] The present inventors have found that, in the case of collectively forming a bipolar electrode laminate by pressing a laminate in which an electrode active material precursor is formed on both sides of a current collector layer, an electrolyte component is added to the electrode active material layer precursor on which the density is desired to be lowered, the laminate is pressed, and then a solvent is added to dissolve the electrolyte component, thereby making it possible to suppress densification of the electrode active material layer caused by pressing.
[0015] Furthermore, according to the method of the present disclosure, by dissolving the electrolyte inside the battery case, the obtained solution can be used as it is as an electrolyte for the battery.
[0016] The method of the present disclosure for producing a bipolar electrode laminate will be described with reference to the drawings. FIG. 1 is a cross-sectional view showing the laminate before dissolving the electrolyte component with a solvent. As shown in FIG. 1, the second electrode active material layer includes a second electrode active material 31 and an electrolyte component 32. FIG. 2 is a cross-sectional view showing the bipolar electrode laminate after dissolving the electrolyte component 32 with a solvent. As shown in FIG. 2, the electrolyte component 32 is dissolved by the solvent to produce an electrolyte solution 40. This makes it possible to suppress densification of the second electrode active material layer by pressing. Note that the first binder and the second binder are omitted in the drawings.
[0017] <Provision of electrode mixture> The method of the present disclosure includes providing a first electrode mix including a first electrode active material and a first binder, and a second electrode mix including a second electrode active material, a second binder, and an electrolyte component.
[0018] (1st electrode composite material) The first electrode mix includes a first electrode active material and a first binder. The first electrode mix also optionally includes a first thickener and a first conductive additive. The first electrode mix can be provided by mixing these materials.
[0019] The first electrode active material is a positive electrode active material or a negative electrode active material. Among known active materials, two materials having different potentials (charge / discharge potentials) at which a predetermined ion is absorbed and released can be selected, and the material exhibiting a more noble potential can be used as the positive electrode active material, and the material exhibiting a less noble potential can be used as the negative electrode active material described below.
[0020] As the positive electrode active material, a known active material may be used. For example, in the case of constructing a lithium ion battery, the positive electrode active material may be lithium cobalt oxide, lithium nickel oxide, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Various lithium-containing composite oxides such as O2, lithium manganate, and spinel-based lithium compounds can be used. In addition, lithium iron phosphate (LFP) can be used as an olivine-type positive electrode active material. The positive electrode active material may be, for example, particulate, and the size of the particulate is not particularly limited.
[0021] As the negative electrode active material, a known active material may be used. For example, in the case of constructing a lithium ion battery, the negative electrode active material may be a silicon-based active material such as silicon, a silicon alloy, or silicon oxide; a carbon-based active material such as graphite or hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, a lithium alloy, or the like. The negative electrode active material may be, for example, particulate, and the size of the particulate is not particularly limited.
[0022] Examples of the first binder include butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, styrene butadiene rubber (SBR)-based binders, acrylate butadiene rubber (ABR)-based binders, polyvinylidene fluoride (PVdF)-based binders, and polytetrafluoroethylene (PTFE)-based binders.
[0023] Examples of the first conductive additive include carbon materials such as acetylene black, ketjen black, and carbon nanotubes, and metal materials such as nickel, aluminum, stainless steel, etc. The conductive additive may be, for example, particulate or fibrous, and its size is not particularly limited.
[0024] The first thickening agent may include, but is not limited to, carboxymethyl cellulose.
[0025] (2nd electrode composite material) The second electrode mixture includes a second electrode active material, a second binder, and an electrolyte component. The second electrode mixture also optionally includes a second thickener and a second conductive agent. The second electrode mixture can be provided by mixing these materials.
[0026] The second electrode active material is one of the positive and negative electrode active materials that forms an electrode active material layer different from that of the first electrode active material. That is, if the first electrode active material is a positive electrode active material, the second electrode active material is a negative electrode active material, and if the first electrode active material is a negative electrode active material, the second electrode active material is a positive electrode active material.
[0027] For the second electrode active material, reference may be made to the above description of the first electrode active material of the present disclosure.
[0028] For the second binder, reference may be made to the above description of the first binder of the present disclosure.
[0029] The electrolyte component may be any material that can function as an electrolyte for a bipolar battery. For example, in the case of a lithium ion battery, the electrolyte component may be a lithium salt. Examples of the lithium salt include lithium bis(fluorosulfonyl)imide (LiFSI) and lithium trifluoromethanesulfonate (LiOTF).
[0030] For the second thickener and the second conductive assistant, reference may be made to the above descriptions regarding the first thickener and the first conductive assistant of the present disclosure.
[0031] <Formation of Electrode Active Material Layer Precursor> The method of the present disclosure includes depositing a first electrode mixture on a first surface of a current collector layer to form a first electrode active material layer precursor, and depositing a second electrode mixture on a second surface of the current collector layer to form a second electrode active material layer precursor, where "electrode active material precursor" in the present disclosure means a layer that can be pressed to form an electrode active material layer.
[0032] (current collector layer) In this disclosure, "current collector layer" means a bipolar current collector layer, i.e., a current collector layer having a positive electrode active material layer formed on one side and a negative electrode active material layer formed on the other side.
[0033] The collector layer may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The collector layer may be made of a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of ease of handling. The collector layer may be made of a plurality of foils. When the collector layer is made of a plurality of metal foils, some layer may be present between the plurality of metal foils.
[0034] When the current collector layer is made of a metal, examples of the metal constituting the current collector layer include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, and stainless steel.
[0035] When the current collector layer is made of a plurality of metal foils, the current collector layer can be formed, for example, by bonding the metal foils together with an adhesive.
[0036] The thickness of the current collector layer is not particularly limited and may be, for example, 0.1 μm or more, or 1 μm or more, and may be 1 mm or less, or 100 μm or less.
[0037] The method of forming a film of the electrode mixture on the surface of the current collector layer may be, for example, a method of applying a paste of the electrode mixture and drying it, but is not limited thereto.
[0038] Pressing the laminate The method of the present disclosure includes pressing a laminate including a first electrode active material layer precursor, a current collector layer, and a second electrode active material layer precursor, for example, using a roll press.
[0039] The pressure with which the laminate is pressed may be 1 kN / cm or more, 3 kN / cm or more, 5 kN / cm or more, 6 kN / cm or more, 7 kN / cm or more, and may be 15 kN / cm or less, 13 kN / cm or less, 11 kN / cm or less, 10 kN / cm or less, 9 kN / cm or less.
[0040] <Dissolution of electrolyte components> The method of the present disclosure includes, after pressing, dissolving the electrolyte components in the second electrode active material layer with a solvent to form an electrolyte solution.
[0041] Examples of the solvent that can be used include carbonates, esters, ethers, nitriles, sulfones, and lactones. Examples of the solvent include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dioxane, 1,3-dioxolane, diethylene glycol, dimethyl ether, ethylene glycol, acetonitrile, propionitrile, nitromethane, N,N-dimethylformamide, dimethyl sulfoxide, sulfolane, and γ-butyrolactone.
[0042] The bipolar electrode stack produced by the method of the present disclosure has, in that order, a first electrode active material layer, a current collector layer, and a second electrode active material layer.
[0043] <First electrode active material layer> In the method of the present disclosure, the first electrode active material layer may be a positive electrode active material layer or a negative electrode active material layer, but is preferably a positive electrode active material layer. In this case, the first electrode active material and the first electrode mixture may be a positive electrode active material and a positive electrode mixture, respectively.
[0044] The density of the first electrode active material layer may be 2.00 g / cc or more, 2.05 g / cc or more, or 2.10 g / cc or more, and may be 2.25 g / cc or less, 2.20 g / cc or less, or 2.15 g / cc or less.
[0045] The difference between the density of the first electrode active material layer and the density of the first electrode active material layer precursor may be 0.20 g / cc or more, 0.25 g / cc or more, or 0.30 g / cc or more, and may be 0.45 g / cc or less, 0.40 g / cc or less, or 0.35 g / cc or less.
[0046] The density can be calculated from the basis weight of the active material and the actual measured thickness.
[0047] The content of each component in the first electrode active material layer may be the same as in the conventional case.
[0048] The shape of the first electrode active material layer may be the same as that of a conventional one. From the viewpoint of making it easier to construct a battery, the first electrode active material layer may be in the form of a sheet.
[0049] The thickness of the first electrode active material layer is not particularly limited. For example, it may be 0.1 μm or more and 2 mm or less. The lower limit may be 1 μm or more, and the upper limit may be 1 mm or less.
[0050] <Current collector layer> For the current collector layer, reference may be made to the above description regarding the current collector layer of the present disclosure.
[0051] <Second electrode active material layer> In the method of the present disclosure, the second electrode active material layer may be a positive electrode active material layer or a negative electrode active material layer, but is preferably a negative electrode active material layer. In this case, the second electrode active material and the second electrode mixture may be a negative electrode active material and a negative electrode mixture, respectively.
[0052] The density of the second electrode active material layer may be 1.00 g / cc or more, 1.05 g / cc or more, or 1.10 g / cc or more, and may be 1.25 g / cc or less, 1.20 g / cc or less, or 1.15 g / cc or less.
[0053] The difference between the density of the second electrode active material layer and the density of the second electrode active material layer precursor may be 0.01 g / cc or more, 0.05 g / cc or more, or 0.08 g / cc or more, and may be 0.20 g / cc or less, 0.15 g / cc or less, or 0.12 g / cc or less.
[0054] The rate of increase from the density of the second electrode active material layer precursor to the density of the second electrode active material may be 0.1% or more, 1.0% or more, 3.0% or more, 5.0% or more, 7.0% or more, 8.0% or more, 9.0% or more, or 9.5% or more, and may be 29.0% or less, 25.0% or less, 20.0% or less, 17.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, or 10.0% or less.
[0055] The content of each component in the second electrode active material layer may be the same as in the conventional case.
[0056] The shape of the second electrode active material layer may be the same as that of a conventional electrode active material layer, but from the viewpoint of making it easier to construct a battery, the second electrode active material layer may be in the form of a sheet.
[0057] The thickness of the second electrode active material layer is not particularly limited. For example, it may be 0.1 μm or more and 2 mm or less. The lower limit may be 1 μm or more, and the upper limit may be 1 mm or less.
[0058] <<Bipolar battery manufacturing method>> The disclosed method of manufacturing a bipolar battery includes manufacturing a bipolar electrode stack.
[0059] <Manufacture of bipolar electrode laminate> For the method of manufacturing the bipolar electrode stack, reference may be made to the above description of the method of manufacturing the bipolar electrode stack of the present disclosure.
[0060] (Storage in a battery case, etc.) A bipolar battery can be obtained by alternately stacking bipolar electrode laminates and separator layers, housing them in a battery case, and impregnating them with an electrolyte. Specifically, the bipolar electrode laminate and separator layer are housed in a battery case, and a solvent that dissolves the electrolyte component in the second electrode active material layer is filled into the battery case to generate an electrolyte, and the bipolar electrode laminate and separator layer are immersed in the electrolyte, and the bipolar electrode laminate and separator layer, as well as the electrolyte, are sealed in the battery case to obtain the bipolar battery of the present disclosure.
[0061] The separator layer may be an electrically insulating nonwoven fabric or a porous film, such as a film made of a resin such as polyethylene (PE) or polypropylene (PP). EXAMPLES
[0062] <<Preparation of bipolar electrode laminate>> <Formation of current collector layer> Example 1 The aluminum foil and the copper foil were bonded together with an adhesive (main agent: olefin-based resin, hardener: isocyanate-based), and the adhesive was subjected to a hardening reaction to form a current collector layer.
[0063] <Formation of Positive Electrode Active Material Layer Precursor and Negative Electrode Active Material Layer Precursor> A positive electrode composite paste was obtained by mixing lithium iron phosphate (LFP) as a positive electrode active material, styrene butadiene rubber (SBR) as a binder, carboxymethyl cellulose (CMC) as a thickener, carbon nanotubes (CNT) as a conductive assistant, and water as a solvent. The obtained positive electrode composite paste was applied to the aluminum foil surface of the current collector layer to form a positive electrode active material layer precursor. In addition, a negative electrode composite paste was obtained by mixing graphite as a negative electrode active material, SBR as a binder, CMC as a thickener, CNT as a conductive assistant, lithium bis(fluorosulfonyl)imide (LiFSI) (manufactured by Nippon Shokubai, Ionel) as an electrolyte component, and water as a solvent. The obtained negative electrode composite paste was applied to the copper foil surface of the current collector layer to form a negative electrode active material layer precursor. The positive electrode active material layer precursor and the negative electrode active material layer precursor formed on the current collector layer were dried to obtain a laminate.
[0064] Pressing the laminate The obtained laminate was pressed with a linear pressure of 8 kN / cm.
[0065] <Dissolution of electrolyte components> The pressed laminate was washed with water to dissolve and remove the LiFSI, thereby producing a bipolar electrode laminate.
[0066] Comparative Example 1 A bipolar electrode laminate was produced in the same manner as in Example 1, except that no electrolyte component was used in forming the negative electrode active material layer precursor, and that no dissolution of the electrolyte component was carried out.
[0067] "evaluation" <density> The densities of the positive electrode active material layer precursor and the positive electrode active material layer, and the negative electrode active material layer precursor and the negative electrode active material layer were measured. The densities were calculated from the basis weight of the active material and the actual measured thickness.
[0068] "result" The calculated density results are shown in Table 1.
[0069] [Table 1]
[0070] As shown in Table 1, the method of the present disclosure was able to suppress an increase in density of the negative electrode active material layer due to pressing, and was able to selectively increase the density of the positive electrode active material layer. [Explanation of symbols]
[0071] 10 First electrode active material layer 11 First electrode active material 20 Current collector layer 30 Second electrode active material layer 31 Second electrode active material 32 Electrolyte components 40 Electrolyte 50 Separator 100 Bipolar Electrodes 1000 Bipolar Battery
Claims
1. 1. A method for producing a bipolar electrode stack having a first electrode active material layer, a current collector layer, and a second electrode active material layer in this order, the method comprising the steps of: providing a first electrode mix comprising a first electrode active material and a first binder, and a second electrode mix comprising a second electrode active material, a second binder, and an electrolyte component; depositing the first electrode mixture on a first surface of the current collector layer to form a first electrode active material layer precursor, and depositing the second electrode mixture on a second surface of the current collector layer to form a second electrode active material layer precursor; pressing a laminate including the first electrode active material layer precursor, the current collector layer, and the second electrode active material layer precursor; and After the pressing, dissolving the electrolyte component in the second electrode active material layer with a solvent to produce an electrolyte solution.
2. The method of claim 1 , wherein the electrolyte component is a lithium salt.
3. 2. The method of claim 1, wherein the first electrode active material layer is a positive electrode active material layer and the second electrode active material layer is a negative electrode active material layer.
4. A method for producing a bipolar battery, comprising producing the bipolar electrode stack by the method of any one of claims 1 to 3.
Citation Information
Patent Citations
Battery
JP2006252882A
Non-aqueous electrolyte battery and manufacturing method of electrode for non-aqueous electrolyte battery
JP2006261041A
Manufacturing method of electrode
JP2020087613A
Bipolar electrode manufacturing method and bipolar electrode
WO2019230323A1
Cited By
Method for manufacturing bipolar electrode stack
CN122930843A
Manufacturing method for bipolar electrode stacks
JP2026167216A
